A highly efficient strategy to determine genotypes of genetically-engineered mice using genomic DNA purified from hair roots. (April 2017) - Otaño-Rivera, Víctor; Boakye, Amma; Grobe, Nadja; Almutairi, Mohammed M; Kursan, Shams; Mattis, Lesan K; Castrop, Hayo; Gurley, Susan B; Elased, Khalid M; Boivin, Gregory P; Di Fulvio, Mauricio
Genotyping of genetically-engineered mice is necessary for the effective design of breeding strategies and identification of mutant mice. This process relies on the identification of DNA markers introduced into genomic sequences of mice, a task usually performed using the polymerase chain reaction (PCR). Clearly, the limiting step in genotyping is isolating pure genomic DNA. Isolation of mouse DNA for genotyping typically involves painful procedures such as tail snip, digit removal, or ear punch. Although the harvesting of hair has previously been proposed as a source of genomic DNA, there has been a perceived complication and reluctance to use this non-painful technique because of low DNA yields and fear of contamination. In this study we developed a simple, economic, and efficient strategy using Chelex® resins to purify genomic DNA from hair roots of mice which are suitable for genotyping. Upon comparison with standard DNA purification methods using a commercially available kit, we demonstrate that Chelex® efficiently and consistently purifies high-quality DNA from hair roots, minimizing pain, shortening time and reducing costs associated with the determination of accurate genotypes. Therefore, the use of hair roots combined with Chelex® is a reliable and more humane alternative for DNA genotyping.